A promising Forcep Strip Method for gastrointestinal subepithelial tumors originating from the muscularis propria. Issue 4 (April 2018) - Yoo, In Kyung; Choi, Hyuk Soon; Chun, Hoon Jai; Kim, Seung Han; Lee, Jae Min; Kim, Eun Sun; Keum, Bora; Lee, Hong Sik; Jeen, Yoon Tae; Kim, Chang Duck
Abstract: Background: Subepithelial tumors (SETs) originating from the muscularis propria layer are unlikely to be resected completely and safely. We developed the Forcep Strip Method (FSM) for the resection of SETs in the stomach. Aims: This study aimed to evaluate the feasibility and safety of the FSM. Methods: Endoscopic SET resection using electrical forceps was performed in 11 consecutive patients with clinical indications for lesion removal. Following injection around the tumor, the adjacent mucosa or submucosa was grasped with the hot forceps and pulled away to form a "tent". The tumor was dissected from the muscularis propria layer and carefully removed using coagulating forceps. Results: The FSM was successful in 10 of the 11 patients in the series; one patient required surgery due to respiratory depression during the procedure. The complete resection rate was 100% and no major complications including bleeding and perforation occurred. Mean procedure time was 39.3 ± 14.7 min, mean hospitalization time was 5.0 ± 1.2 days, and mean tumor size was 17.1 ± 4.7 mm. Conclusion: FSM was found to be an easy, safe, and effective procedure for the treatment of gastric SETs originating from the muscularis propria layer.